PENGARUH IKLIM ORGANISASI, KEPEMIMPINAN TRANSFORMASIONAL, SELF EFFICACY TERHADAP PERILAKU KERJA INOVATIF - Aditya, Dewa Nyoman Reza; Ardana, Komang (E-Jurnal Manajemen; Vol 5 No 3 (2016), 2016)
Innovative work behavior is an introduced attitude, filed, applying ideas, products, processes, and procedures to the new job. An organization needs to pay attention to the factors that influence innovative work behavior. The aim of this study is to investigate the impact of organizational climate, transformational leadership, and self efficacy on innovative work behavior of PT. Serasi Autoraya Denpasar Branch employees. The number of respondent is 34 employees determinated through non probability sampling method, saturated sampling specially. Data is collected through interviews and questionnaires. The analysis technique used is multiple linear regression. The results show that organizational climate, transformational leadership, and self efficacy have positive effect on employee innovative work behavior. This shows that the better the perceived organizational climate , the stronger transformational leadership, and the higher self efficacy of employees will increase innovative work behavior of employees.
Keywords: innovative work behavior; organizational climate; transformational leadership; self efficacy